The Effects of Unani Formulation Jawarish Bisbasa in Dyslipidaemia and Anthropometric Parameters Associated with Central Obesity- An open-label clinical Trial (Indian Journal of Public Health Research & Development, 2024)
Abstract:The Unani system of medicine is endowed with enormous single and compound drugs and regimes for managing obesity that are safe and effective. Jawarish Bisbasa, a Unani polyherbal formulation, is traditionally used in the clinical treatment of central obesity. It is a polyherbal, semi-solid preparation of eleven medicinal herbs mainly used as spices. Though the standardized operating procedure for preparing Jawarish Bisbasa and its quality evaluation, along with stability data, have been reported, scientific documentation of the data on the safety and pharmacokinetic profile of Jawarish Bisbasa remains unexplored. One known modifiable risk factor for ischemic heart disease, stroke, and hypertension is dyslipidemia. The limitations of current conventional therapy have provided scope for research into a potential drug for this medical condition. It was hypothesized that Unani Formulation Jawarish Bisbasa may ameliorate dyslipidemia in humans.Aim of the study: The main objective of this study was to evaluate the effect of Unani Formulation Jawarish Bisbasa and compare the changes in lipid profiles and anthropometric parameters before and after treatment in patients with hyperlipidemia associated with central obesity.Materials and methods: An open-label clinical validation study was conducted at the Regional Research Institute of Unani Medicine, Mumbai Research OPD. The study included 120 cases of each gender with BMIs of 34.99 kg/m2 for men and 32.49 kg/m2 for women, while 88 cases completed the study. Enrolled cases received Unani Formulation Jawarish Bisbasa 7gm BD twice daily with warm water for 8 weeks. The pathological investigations and anthropometric parameters related to the study, particularly BMI, waist circumference, waist-to-hip ratio, sagittal abdominal diameter, LDL, HDL, and VLDL values, were statistically analyzed at baseline, first, follow-up, and at the end of the study by using an unpaired Student t-test and one-way analysis of variance. (ANOVA). Extremely significant BMI, waist circumference, waist-to-hip ratio, sagittal abdominal diameter, and lowering of ESR, total cholesterol, and triglycerides were analyzed in hyperlipidemia associated with central obesity. There were no side effects reported during the treatment.
Keywords: Hypertension, BMI,Central obesity, salt intake; bmi, hyperlipidemia